2018
DOI: 10.1111/echo.14051
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial function: Correlation with left ventricular function and contractile reserve in patients with hypertension

Abstract: Compared to controls, hypertensive patients had impaired LA strain, which correlated with LV GLS and CR. LV GLS and LAVImax were the strongest independent determinants for LA Ɛs/Ɛe and LA Ɛa, respectively, independent of BP and LVMi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…Our study found impaired LA reservoir (decreased εs and SRs) and conduit (decreased εe and SRe) functions in HTN(MR−) patients compared to the controls. This finding conforms to previous reports on hypertensive cases 20,28 . However, the LAV and LAEF were unchanged.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found impaired LA reservoir (decreased εs and SRs) and conduit (decreased εe and SRe) functions in HTN(MR−) patients compared to the controls. This finding conforms to previous reports on hypertensive cases 20,28 . However, the LAV and LAEF were unchanged.…”
Section: Discussionsupporting
confidence: 93%
“…This finding conforms to previous reports on hypertensive cases. 20,28 However, the LAV and LAEF were unchanged. Kokubu et al reported that treatment of hypertension with reninangiotensin system inhibitors restored the LA reservoir strain only when the LA was not enlarged.…”
Section: Characteristics Of La and LV Impairment In Hypertensive Casesmentioning
confidence: 95%
“…Systemic hypertension and diabetes have been shown to be associated with early reduction of all LA myocardial deformation components in subjects with normal LA dimensions (111). In hypertensive patients, the impairment of reservoir, conduit, and contractile function has been related to LV global longitudinal strain (GLS) and contractile reserve explored by dobutamine stress test and confirming the interplay between LA and LV function (112). However, the relationship between LA and LV function is stronger when atrial chamber is not dilated and seems to be less relevant when LA dilatation occurs (113,114).…”
Section: La Mechanics In Hf Stages Stage Amentioning
confidence: 92%
“…New echocardiographic parameters such as strain and the strain rate (SR) are closely related to the functional state of the LA and more sensitive in the early detection of its subtle changes . Strain and the SR represent the magnitude and rate of myocardial deformation .…”
mentioning
confidence: 99%
“…New echocardiographic parameters such as strain and the strain rate (SR) are closely related to the functional state of the LA and more sensitive in the early detection of its subtle changes. 3,6,7 Strain and the SR represent the magnitude and rate of myocardial deformation. 8 Left atrial strain profiles show 3 LA aspects: passive strain (LA conduit function), active strain (LA pump function), and total strain (LA reservoir function).…”
mentioning
confidence: 99%